Efficacy of Vismodegib in pigmented basal cell carcinoma: Appearances are deceiving. Issue 6 (18th August 2020) - Di Raimondo, Cosimo; Mazzeo, Mauro; Di Prete, Monia; Lombardo, Paolo; Silvaggio, Dionisio; Del Duca, Ester; Bianchi, Luca; Spallone, Giulia
Abstract: Basal cell carcinoma (BCC) is the most common skin cancer in humans. Pigmented basal cell carcinoma (pBCC) is a rare variant of BCC. Vismodegib, was the first drug to be approved for the treatment of locally advanced (laBCCs) or metastatic basal cell carcinoma. The aim of this study was to evaluate the efficacy of Vismodegib in patients with pBCCs. We retrospectively analyzed patients receiving Vismodegib as treatment for laBCCs presenting also various pBCCs. After 6 months of treatment, we performed excisional biopsies of pBCCs, that apparently at clinical and dermoscopic assessment did not respond to therapy. A total of nine patients were assessed. After 6 months of treatment, locally advanced target BCCs showed complete remission in four out of nine patients (44.4%), four patients (44.4%) were considered in partial remission and one patient (11%) showed no response to treatment. On the contrary, all the pBCCs showed both clinically and dermoscopically resistance to treatment. Therefore, clinically persistent pBCCs were surgically removed in three patients. Histology showed a complete elimination of the neoplastic cells together with features of previous regression. Our findings indicate that the efficacy of Vismodegib is higher than that documented by clinical or even dermatoscopic observation alone.